Health Assessment of Livistona chinensis and Cycas revoluta in UNIMAS - Siti Nadhirah, binti Ismail (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Urban trees planted in the urban landscape are usually beautiful, of high aesthetic values and should be free from pest and diseases. However, due to several biotic and abiotic factors, urban trees are sometimes infected with pest and diseases. The objective of this study is to assess the health status of 69 Livistona chinensis (Chinese Palm) and 24 Cycas revoluta (Cycad Palm) planted in different sites within UNIMAS campus. In this study, the health assessment of the palms were measured including of DBH, height, planting distance, chlorophyll content, health status and symptoms of infection. The infected part of palm with Ganoderma conk formation was the indicator that the palm was affected by Ganoderma butt rot disease. Overall, Chinese Palm planted in UNIMAS was in good condition although suffering with nitrogen deficiencies and attacked by palm borer beetle while Cycad Palm was in fair condition probably due to potassium deficiencies and Ganoderma butt rot disease. This health assessment will aids the management in UNIMAS in planning a more proper palm health management.